Exploring the Expansion and Future Horizons of AdTech Industry - Chauhan, Devratan (ATLAS SkillTech University, 2025)
AdTech stands for Advertising Technology, a fast-moving digital marketplace where businesses and advertisers are continually trying to find innovative ways to get to and engage consumers. It is all about advanced technology that makes advertising smarter, more targeted, and effective. At the very centre of this industry lies technology and data. It's the engine that runs everything in the world of AdTech. Companies use advanced tools and data analysis to know what piques a consumer's interest, what they do online, and how they make purchasing decisions. Businesses use this data to craft highly targeted advertisements so you see only what's relevant to your interests or needs. Say, you were in search of new running shoes, and all of a sudden you started seeing the ads for athletic wear or specific sneaker sales; this is how the targeted advertising is supposed to grab your attention by including all the significant contents.
Project Report on Exploring the Expansion and Future Horizons of AdTech Industry (2023-2025) Under the Guidance of Prof. Anand Kopare
Keywords: Advertising Technology; digital marketplace; advertisers; AdTech